Effects of high-intensity training by heart rate or power in well-trained cyclists - Swart, J.; Lamberts, R. P.; Derman, W.; Lambert, M. I. (The Journal of Strength and Conditioning Research, 2009)
The aim of this study was to determine whether the performance of cyclists after 4 weeks of high-intensity training improved similarly using either heart rate or power to prescribe training. Twenty-one well-trained men cyclists (age, 32 ± 6 years; peak power output, 371 ± 46 W) were randomly assigned to a power-based (GPOWER) or heart rate-based (GHEART) high-intensity training (HIT) group or a control group (GCONTROL). Training consisted of 8 repetitions of 4 minutes at either 80% of peak power output (GPOWER) or at the heart rate coinciding with 80% of peak power output (GHEART), with rest periods of 90 seconds. A 40-km time trial and Vo2max test were performed before and after 8 training sessions. There were significant improvements (p < 0.05) in peak power output (GPOWER = 3.5%; GHEART = 5.0%) and 40-km time trial performance (GPOWER = 2.3%; GHEART = 2.1%) for both of the high-intensity groups. Although there were no significant differences between groups for these variables, when the data were analyzed using magnitude-based effects, the GHEART group showed greater probability of a beneficial effect for peak power output. The current general perception that prescribing training based only on power is more effective than prescribing training based on heart rate was not supported by the data from this study. Coaches who are unable to monitor progress frequently should prescribe training based on heart rate, when intervals are performed under stable conditions, because this may provide an additional advantage over prescribing training using power.